Physicochemical Characterisation And Dissolution Properties Of Spironolactone Solid Binary Systems - Arali , Bharati; Devaraj, Pruthvi; A Patil, Uma; Madhu , A (Asian Journal of Pharmaceutical Research and Development, 2024)
Objective: To study the physicochemical characterisation and dissolution properties of Spironolactone complexing it with β-Cyclodextrin and Hydroxypropyl-β-Cyclodextrin in different molar ratios (1:1 M and 1:2 M). Design Interventions: Spironolactone belonging to BCS class II, exhibits low and variable oral bioavailability due to its poor aqueous solubility. Enhancement in solubility and dissolution rate leads to an increase in its oral bioavailability. Solid binary systems were prepared by Physical mixture, Kneading method, Microwave irradiation and Freeze-drying method. They were evaluated by in vitro dissolution studies and characterised using different analytical techniques. Main Outcome Measures: The host guest interactions studied by different techniques confirmed true inclusion of Spironolactone with β-Cyclodextrin and Hydroxypropyl-β-Cyclodextrin at 1:1 M and 1:2 M. Results: Overall, the rank order of improvement in dissolution properties of Spironolactone with ratios is 1:2 M > 1:1 M, methods Freeze-drying > Microwave irradiation > Kneading method > Physical mixture and complexing agent Hydroxypropyl-β-Cyclodextrin > β-Cyclodextrin. Conclusion: Among the developed Spironolactone SBSs, the SBS prepared with HP- βCD of 1:2 M ratio by Freeze drying method showed good result in dissolution study which shows the maximum release of drug in the range of 95.6%.